PENGARUH GAYA KEPEMIMPINAN TERHADAP PRODUKTIVITAS WAREHOUSE PT. THIESS site Melak, Kutai Barat - -, Teofilus Erimansyah (EKONOMIA, 2015)
Human resources are the most strategic element in the organization, must be recognized and accepted management . Increased productivity may only be done by humans. Instead of human resources that can also be the cause of waste and inefficiency in its various forms ( Siagian , 2002) . Because it gives attention to the human element is one of the demands in the overall effort to increase labor productivit, Terry ( 1960), assume leadership as activities to influence people to work with willing to achieve a common goal . Broadly defined leadership as an organized effort to manage and utilize human resources, material, and financial in order to achieve the stated goals ( Zainun , 1979). The Bass and Stogdill (1990 ) , says that leadership is a process of influencing the activities of a group in an effort to achieve the goals set . In addition, a leader figure is expected to run a leadership function properly by applying leadership style , and formulate what style of leadership , based on the description / explanation above, the researcher aims to identify and analyze the participative leadership style ( X1 ) , persuasive ( X2 ) , motivational ( X3 ) , and educational ( X4 ) significantly affects the productivity of warehouse PT . Thiess , site Melak , West Kutai.To facilitate data analysis of this study , the data obtained should be simplified in advance . To determine whether there is influence between the variables examined, the researchers used the classical assumption test and to determine the accuracy of prediction of whether there is a strong relationship between the dependent variable ( Y ) employee productivity with the independent variable ( X ) leadership style, so in this study using multiple linear regression analysis . With the research hypothesis testing reject or accept the hypothesis being tested .By using a multiple linear regression analysis and hypothesis testing, it can be concluded that the hypothesis is accepted , that the motivational leadership style, and educational , the most dominant influence on the productivity of warehouse PT. Thiess, site Melak , Kutai Barat.